A New Device for Securing Sternal Wires after Median Sternotomy: Biomechanical Study and Retrospective Clinical Assessment. Issue 1 (January 2018) - Danter, Matthew R.; Saari, Amy; Gao, Min; Cheung, Anson; Lichtenstein, Samuel V.; Abel, James G.
Objective: Morbidity due to sternotomy continues to be a significant clinical problem. Poor approximation of the sternum may lead to complications such as sternal dehiscence, infection, and pain. A device to assist in tensioning and twisting standard steel wires during sternal closure has been developed (TORQ TM sternal closure device). Manually tightened interrupted wire closures were compared with those tightened and secured with the aid of the device. Performance of the device was assessed clinically. Methods: Four cardiovascular surgeons performed manual and device-assisted closures on a biofidelic model. Closure force was measured to determine the residual force and its intraoperator variation. A retrospective review of patients treated before and after the introduction of the device was conducted. Predicted and actual outcomes were compared for the two groups (manual closure and deviceassisted closure). Results: Biomechanical testing measured a 75% increase in residual closure force ( P < 0.001) and a significant reduction in the variability of the closure force ( P = 0.045) for device-assisted closures compared with manual closures. In the retrospective study, 3 of 173 manually closed patients had sterile sternal dehiscence and 1 of 173 had a deep sternal wound infection. In the device closure group, 2 of 127 had a sterile sternal dehiscence and no deep sternal wound infections were reported. No other device-related serious adverse events were reported. Conclusions: Biomechanical data showed stronger, more consistent closure forces with the device. The retrospective data attest to the performance of the device.